Novel concept of exosome-like liposomes for the treatment of Alzheimer's disease - Fernandes, Mário (2021)
Exosomes are cell-derived vesicles that act as carriers for proteins and nucleic acids, with therapeutic potential and high biocompatibility. We propose a new concept of exosome-like liposomes for controlled delivery. The goal of this work was to develop a new type of liposomes with a unique mixture of phospholipids, similar to naturally occurring exosomes but overcoming their limitations of heterogeneity and low productivity, for therapeutic delivery of bioactive compounds. Curcumin was chosen as model compound, as it is a phytochemical molecule known to have antioxidant and anti-inflammatory properties, which can protect the brain against oxidative stress and reduce β-amyloid accumulation, major hallmarks of Alzheimer's disease (AD). These new liposomes can efficiently encapsulate hydrophobic curcumin, yielding particles with a size smaller than 200 nm, and a polydispersity index lower than 0.20, which make them ideal for crossing the blood-brain barrier. These particles have a long shelf life, being stable up to 6 months. The curcumin encapsulation efficiency was higher than 85% (up to approximately 94%). Curcumin-loaded liposomes were not cytotoxic (up to 20 μM curcumin, and 200 μM of exo-liposomes), and significantly reduced oxidative stress induced in SH-SY5Y neuronal cells, indicating their potential for neuroprotection. They also do not show any toxicity and are internalized in zebrafish embryos, concentrating in lipid enriched areas, as the brain and the yolk sac. Such innovative carriers are a new effective approach to deliver drugs into the brain, as these are stable, protect the cargo and are uptaken by neuronal cells. Upon internalization, liposomes release the therapeutic biomolecules, resulting in successful neuroprotection, being a positive alternative strategy for AD therapy.